The Effect of Addition Mn2+ Metal Ions and Incubation Time to Bacillus cereus Cellulase Enzyme Activity from Endophytic Bacteria of Curcuma Rhizome (Curcuma zanthorrizha Roxb.) - Sulistyantini, Cahyaning; Utami, Ulfah (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2021)
Cellulase is one of the most widely used enzymes in the industrial world and wastes decomposition process. Bacillus cereus is one of the bacteria that can produce cellulase enzymes that can hydrolyze cellulose to glucose. The addition of cofactors and incubation time can help determine the optimum conditions needed by cellulase enzymes to work optimally. This study aims to determine the effect of adding Mn2+ metal ions and incubation time to the activity of cellulase enzymes from Bacillus cereus endophytic bacteria. This research is experimentally used a Completely Randomized Design (CRD) factorial design with two factor treatments and 3 times repetitions. The first factor is variation of addition Mn2+ metal ions which are 5 mM, 10 mM, and 15 mM, the second is variation of incubation time which are 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours. The data were analyzed using Analysis Of Variance (ANOVA) and if the data significantly affected the parameter, then it would be continued by Duncan Multiple Range Test (DMRT) with the fault level of 5%. The result showed that the interaction of addition Mn2+ metal ions and incubation time affected the cellulase enzyme activity of Bacillus cereus from endophytic bacteria. The highest cellulase enzyme activity obtained from interaction addition Mn2+ metal 10 mM and incubation time 3 hours with an activity 0,335 U/mL, while the lowest cellulase enzyme activity obtained from interaction addition Mn2+ metal 15 mM and incubation time 5 hours with an activity of 0,073 U/mL